To study the thyroid profile in menstrual disorder at tertiary care hospital in northern western Rajasthan, India - Jinger, Surendra Kumar; Verma, Anita; Dayma, Indu; Talreja, Tamanna (International Journal of Research in Medical Sciences, 2017)
Background: Abnormal uterine bleeding is a common but complicated clinical presentation. It is one of the most frequently encountered conditions in gynaecology and is defined as abnormal bleeding from the uterus. Methods: Present prospective study was conducted on 100 patients who presented with abnormal uterine bleeding at Sardar Patel Medical College, Bikaner, Rajasthan, India. Results: Among 100 women, 39 had hypothyroidism, 8 patients had hyperthyroidism rest 53 were euthyroid. Out of 39 hypothyroid patients, 23 had menorrhagia, 3 had oligomenorrhea and out of 8 patients with hyperthyroidism patients, 6 had oligomenorrhea, 2 had hypomenorrhoea. Conclusions: The menstrual irregularities are significantly more frequent in patients with thyroid dysfunction and menorrhagia was the commonest menstrual abnormality. The study concludes that biochemical evaluation of thyroid function should be made mandatory in all cases of AUB.